Research on acoustic sensing device based on microfiber knot resonator. (1st August 2022) - Zhao, Rongyu; Cui, Jiangong; Yu, Yaxin; Zhai, Xiaoping; Chu, Xiaoxia; Zhu, Min; Wu, Bofeng; Yang, Yuhua; Wang, Renxin; He, Changde; Zhang, Guojun; Zhang, Wendong
Abstract: An acoustic sensor packaged with polydimethylsiloxane film sandwich structure is proposed in this paper. The sensor uses a flat glass with a square hole in the middle as the substrate structure. The cavity length of the microfiber knot resonator is significantly changed by the applied acoustic pressure, which is ultimately manifested as a change in the strength of the sensor signal. The sensor has a good response at frequencies from 0.1 to 10 kHz, and has a sensitivity of 0.92 mV Pa −1 at 1 kHz acoustic frequency. The sensor studied in this paper has the advantages of wide frequency band, small size and low cost, and has a good application prospect in the field of acoustic signal detection.